2017
DOI: 10.3389/fneur.2017.00557
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Dysfunction and Difficulty with Driving: Data from the 2001–2004 National Health and Nutrition Examination Surveys

Abstract: Background and objective:There is growing understanding of the role of vestibular function in spatial navigation and orientation. Individuals with vestibular dysfunction demonstrate impaired performance on static and dynamic tests of spatial cognition, but there is sparse literature characterizing how these impairments might affect individuals in the real-world. Given the important role of visuospatial ability in driving a motor vehicle, we sought to evaluate whether individuals with vestibular dysfunction mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…More generally, Wei and Agrawal (2017) reported from a study of driving difficulty associated with vestibular dysfunction that women exhibited greater difficulty driving than men (P Յ 0.0013). In a study of cognitive performance in patients with vestibular loss and Alzheimer's disease, they reported that women performed worse in the Money Road Map Test than men, making 6.4 more errors (95% CI: 2.1-10.6; Wei et al 2018).…”
Section: Bilateral Vestibular Lossmentioning
confidence: 95%
“…More generally, Wei and Agrawal (2017) reported from a study of driving difficulty associated with vestibular dysfunction that women exhibited greater difficulty driving than men (P Յ 0.0013). In a study of cognitive performance in patients with vestibular loss and Alzheimer's disease, they reported that women performed worse in the Money Road Map Test than men, making 6.4 more errors (95% CI: 2.1-10.6; Wei et al 2018).…”
Section: Bilateral Vestibular Lossmentioning
confidence: 95%
“…Individuals with a vestibular disorder had difficulty driving under conditions where useful visual cues were reduced, precise spatial navigation skills were needed, and rapid head movements were elicited, and they reported having to pull off the road due to vertigo in some cases. In an analysis of data from the 2001-2004 National Health and Nutrition Examination Survey study, Wei et al 47 evaluated the influence of vestibular dysfunction on driving difficulty in Americans aged ≥50 years (N = 3071). They found that vestibular dysfunction was associated with self-reported driving difficulty; those with clinically symptomatic (vs self-reported) vestibular dysfunction had a 4-fold increase in odds of reporting difficulty with driving.…”
Section: Impact Of Migraine Symptoms On Driving Perfor-mentioning
confidence: 99%
“…Studies in patients with specific vestibular disorders found that 60% of patients with Menière’s disease found driving to be either difficult or dangerous to perform [37], and 30% of patients with vestibular schwannomas experienced driving difficulty following surgical resection of their tumors [38]. Recently published data from the National Health and Nutrition Examination Survey (NHANES) found that individuals with symptomatic vestibular dysfunction had an over four-fold odds of experiencing driving difficulty relative to individuals without vestibular dysfunction [39]. Furthermore, when assessing specific driving conditions, one study found that vestibular patients have particularly greater difficulty with driving tasks that require spatial navigation such as changing lanes in traffic, staying in lane, and pulling into or out of parking spaces as well as with driving tasks where vision was limited such as driving at night or in the rain [40].…”
Section: Discussionmentioning
confidence: 99%